Pattern of Drug Information Sources Utilized by Medical Practitioners at A Teaching Hospital in Nepal - Prasad, Pravin; Karki, Naresh; Kandel, Kamal; Shah, Shruti; Muskan, Vitasta; Ghimire, Rakesh; Mudvari, Anis; Gyanwali, Pradip (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: The development of pharmaceutical industry has been adding new knowledge about drugs continuously making it difficult to remember each piece of information. The physicians need to be supplemented with new information using various unbiased and reliable drug information (DI) sources which will promote rationale use of medicines. This study aims to understand the commonly used sources of DI by prescribers at our institute, their usefulness and the need for an independent drug information unit at the institute. Methods: A cross-sectional descriptive study that included all prescribers presently working at this institute and actively involved in patient care was conducted. Consenting participants were requested to fill in the self-administered questionnaire. Data thus collected were entered using EpiData version 3.1 and were analysed using SPSS version 18. Results: Filled-in questionnaires were obtained from 147 prescribers. Almost all of the participants (95.80%) used textbooks and Online Medical Sites (OMS) as sources of DI. Among participants using OMS for DI, 80 (58.39%) classified them as sometimes biased. Less than half (41.25%) agreed that they will absolutely be benefitted from having unbiased DI services at the hospital. The participants most commonly (136, 92.50%) had queries related to dosage / administration on a daily basis. Conclusions: Most prescribers relied on textbooks and OMS for DI which in their opinion had some level of biasness associated with them. They also agreed on the need of independent DI services in the institution to support prescription practices.